2022
DOI: 10.1002/anie.202203448
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/Copper‐Cocatalyzed Asymmetric Benzylation of Aldimine Esters for the Enantioselective Synthesis of α‐Quaternary Amino Acids

Abstract: The first asymmetric Ni/Cu cocatalyzed benzylation of aldimine esters is reported. A series of benzylsubstituted α-quaternary amino acids could be synthesized in high yield and with high levels of enantioselectivity (up to 90 % yield and 99 % ee). The experimental and theoretical calculation results suggested that the strong electrophilicity of the η 3 -benzylnickel intermediate is crucial for the high reactivity, enabling the reaction under base-free conditions. Furthermore, this method has been applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Additionally, the problem of the entropic penalty associated to bond‐forming reactions that require various molecules in dual catalytic system leads to low reactivity. Recently, the theoretical calculation study suggested that attractive noncovalent interactions between the two catalysts and substrates have been recognized to have an important influence on the reactivity and stereoselectivity, which will compensate the above‐mentioned adverse effects [11r–t,21l–n,64] …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the problem of the entropic penalty associated to bond‐forming reactions that require various molecules in dual catalytic system leads to low reactivity. Recently, the theoretical calculation study suggested that attractive noncovalent interactions between the two catalysts and substrates have been recognized to have an important influence on the reactivity and stereoselectivity, which will compensate the above‐mentioned adverse effects [11r–t,21l–n,64] …”
Section: Discussionmentioning
confidence: 99%
“…Zhang and co-workers reported bimetallic Ni/Cu-cocatalyzed asymmetric benzylation of aldimine esters to prepare α-quaternary amino acids (Scheme ), a functional group present in several molecules of medicinal interest. The authors pointed out that while several examples of precious metal/precious metal- and precious metal/nonprecious metal-cocatalyzed reactions have been reported, examples of nonprecious metal/nonprecious metal-cocatalyzed reactions are rare. , ( R )-BINAP was identified as the optimal ligand for Ni and ( S , S p )-phosferrox for Cu.…”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…In 2018, Snaddon and co-workers introduced benzotetramisole/Pd cooperatively catalyzed asymmetric benzylation reactions of acetic acid esters ( 21 ). Most recently, two highly efficient examples of asymmetric benzylation of azomethine ylides enabled by dual metal catalysis have been reported by the Zhang group ( 23 ) and the Wang group ( 24 ), respectively. Recently, Guo and co-workers established an α-benzylation reaction of N-unprotected amino acids with excellent stereocontrol ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Trost and co-workers successfully demonstrated a model approach for the asymmetric benzylation of prochiral carbon nucleophiles via palladium catalysis (12)(13)(14). Very recently, asymmetric benzylic substitutions accomplished through a cooperative combination (15)(16)(17)(18)(19)(20) of isoelectronic π-benzyl palladium/nickel species with chiral organocatalysts (21,22) or Lewis acids (23,24) that mediated nucleophiles have greatly progressed. In 2018, Snaddon and coworkers introduced benzotetramisole/Pd cooperatively catalyzed asymmetric benzylation reactions of acetic acid esters (21).…”
Section: Introductionmentioning
confidence: 99%